2016
DOI: 10.1021/acs.molpharmaceut.6b00102
|View full text |Cite
|
Sign up to set email alerts
|

Post-PEGylation of siRNA Lipo-oligoamino Amide Polyplexes Using Tetra-glutamylated Folic Acid as Ligand for Receptor-Targeted Delivery

Abstract: For efficient and receptor-specific siRNA delivery, a new post-PEGylation strategy was established to provide siRNA polyplexes with targeting and shielding agents. For this purpose, core nanoparticles were formed by complexing siRNA with sequence-defined cationic lipo-oligomers. The T-shaped bis-oleoyl-oligoethanamino amides 454 and 595, containing stabilizing tyrosine and cysteine residues, were applied. These core nanoparticles were surface-shielded by reaction with maleimido-polyethylene glycol (Mal-PEG) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 83 publications
5
31
0
Order By: Relevance
“…For postintegration into core lipopolyplexes, the bivalent structure Cys(Npys) 2 ‐PEG 24 ‐GE11 was found to be the best agent, yielding highly specific, EGFR dependent gene transfer, demonstrated with luciferase marker gene and sodium iodide symporter (NIS) gene expression studies. Previous work already pointed out that postmodification represents a promising tool for shielding and targeting pDNA as well as siRNA polyplexes . The superior effect of the bivalent over monovalent linkage is well consistent with similar findings using multivalent coatings of nucleic acid nanoparticles …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For postintegration into core lipopolyplexes, the bivalent structure Cys(Npys) 2 ‐PEG 24 ‐GE11 was found to be the best agent, yielding highly specific, EGFR dependent gene transfer, demonstrated with luciferase marker gene and sodium iodide symporter (NIS) gene expression studies. Previous work already pointed out that postmodification represents a promising tool for shielding and targeting pDNA as well as siRNA polyplexes . The superior effect of the bivalent over monovalent linkage is well consistent with similar findings using multivalent coatings of nucleic acid nanoparticles …”
Section: Discussionsupporting
confidence: 86%
“…Peripheral tyrosine trimers (Y 3 ) increase polyplex stability via interoligomeral π–π stacking of aromatic rings; C‐terminal as well as N‐terminal cysteine residues provide additional, disulfide triggered polyplex stabilization as well as anchors for the subsequent post‐PEGylation. This oligomer has been extensively investigated as core oligomer for receptor dependent siRNA delivery in vitro as well as in vivo, e.g., via folate receptor, transferrin receptor as well as EGFR, but has been never used as core carrier for receptor targeted pDNA delivery. Pre‐PEGylation of 454 before polyplex formation was unsuccessful, resulting in polyplex aggregation (SM, unpublished results).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the cells treated with standard siGFP polyplexes, the silencing effect was significantly decreased (45-63% for TCPs and 35% for 356), further highlighting that Inf7 peptide is necessary for sufficient release of siRNA into cytosol, as previously reported earlier [16,35,36]. Besides, recently we verified that the uptake of 100-200 nm FR-targeted polyplexes could be blocked completely by excess free folate, while the agglomerated large particles (>200 nm) might partially undergo receptor-independent uptake and gene silencing [61]. The luciferase activity in KB/eGFPLuc cells treated with controls, including siCtrl polyplexes and siCtrl-Inf7 polyplexes were similar to untreated cells, which suggested that there is no intrinsic cytotoxicity of TCPs.…”
Section: Gene Silencing Efficiency Of Tcpssupporting
confidence: 85%
“…The polyplexes formed by crosslinking were hypothesized to be more metabolically stabilized in circulation than the noncrosslinked polyplexes. In addition, post-PEGylation of sulfhydryl crosslinked polyplexes was performed to limit the amount of PEG on the surface of the polyplex because too much PEG could limit transfection efficiency 221 . The C-C(depro) was incubated for 1 hr in a pH neutral buffer with dsmRNA and then PEGylated with 10 eq mPEGmal5kDa.…”
Section: Effect Of Sulfhydryl Crosslinking On Dsmrna Circulatory Stabmentioning
confidence: 99%